Fyn tyrosine kinase, a downstream target of receptor tyrosine kinases, modulates antiglioma immune responses. Issue 6 (17th January 2020) - Comba, Andrea; Dunn, Patrick J; Argento, Anna E; Kadiyala, Padma; Ventosa, Maria; Patel, Priti; Zamler, Daniel B; Núñez, Felipe J; Zhao, Lili; Castro, Maria G; Lowenstein, Pedro R
Abstract: Background: High-grade gliomas are aggressive and immunosuppressive brain tumors. Molecular mechanisms that regulate the inhibitory immune tumor microenvironment (TME) and glioma progression remain poorly understood. Fyn tyrosine kinase is a downstream target of the oncogenic receptor tyrosine kinase pathway and is overexpressed in human gliomas. Fyn's role in vivo in glioma growth remains unknown. We investigated whether Fyn regulates glioma initiation, growth and invasion. Methods: We evaluated the role of Fyn using genetically engineered mouse glioma models (GEMMs). We also generated Fyn knockdown stem cells to induce gliomas in immune-competent and immune-deficient mice (nonobese diabetic severe combined immunodeficient gamma mice [NSG], CD8−/−, CD4−/−). We analyzed molecular mechanism by RNA sequencing and bioinformatics analysis. Flow cytometry was used to characterize immune cellular infiltrates in the Fyn knockdown glioma TME. Results: We demonstrate that Fyn knockdown in diverse immune-competent GEMMs of glioma reduced tumor progression and significantly increased survival. Gene ontology (GO) analysis of differentially expressed genes in wild-type versus Fyn knockdown gliomas showed enrichment of GOs related to immune reactivity. However, in NSG and CD8−/− and CD4−/− immune-deficient mice, Fyn knockdown gliomas failed to show differences in survival. These data suggest that the expression of Fyn in glioma cells reduces antiglioma immune activation. Examination of glioma immune infiltrates by flow cytometry displayed reduction in the amount and activity of immune suppressive myeloid derived cells in the Fyn glioma TME. Conclusions: Gliomas employ Fyn mediated mechanisms to enhance immune suppression and promote tumor progression. We propose that Fyn inhibition within glioma cells could improve the efficacy of antiglioma immunotherapies.